Digital Disruption and Author Strategy: A Qualitative Study of Self-Publishing in the US Science Fiction and Fantasy Market as a Source of Intangible Assets - Bobek, Vito; Elliot, Jacob; Horvat, Tatjana (Naše gospodarstvo/Our economy, 2025)
This paper examines how self-published authors in the U.S. science fiction and fantasy (SFF) market strategically respond to digital disruption in the publishing industry. Drawing on fifteen expert interviews analyzed through Mayring’s qualitative content analysis, the study integrates four theoretical perspectives: disruptive innovation, diffusion of innovations, the resource-based view, and actor-network theory. The results show that independent authors act as entrepreneurial micro-firms, leveraging intangible assets such as brand identity, digital marketing skills, and reader communities to navigate platform-based markets. Authors adopt funnel marketing, hybrid publishing, and platform-specific strategies to enhance visibility and monetise creative output. The sample is limited to one genre and national context, and findings are therefore exploratory. The study advances our understanding of cultural entrepreneurship and platform economies by demonstrating how digitalisation reconfigures authorial agency within sociotechnical networks of platforms, algorithms, and digital tools.
Keywords: Digital disruption; Author strategy; Science fiction and fantasy; Cultural entrepreneurship; Platform economy; Publishing industry; Intangible Assets